Defining quality education in higher learning institutions: divergent views of stakeholders - Anis, Azilah; Abdullah, Zainah; Islam, Rafikul (University Publicatons. net, 2014)
Quality education is an indicator for an institution's ability to provide tertiary education for the society besides being an instrument for the nation's economic growth. While numerous studies have been conducted in measuring the quality of education in higher learning institutions, defining the term has largely been contested, considerably vague and highly contextual, efforts should be invested in acquiring the definition for them particularly from the various perspectives of the stakeholders of higher learning institutions. To this end, the present study was conducted by applying the qualitative approach to obtain views from the stakeholders of various Malaysian private higher learning institutions. Twenty three respondents ranging from the quality directors of the institutions, authorised personnel in tertiary education, related government agencies, representatives of the National Association of Private Educational Institutions, employees of the institutions such as senior lecturers and administrative staff, students, prospective employers as well as parents, were interviewed. Content analysis was then utilised to analyse the feedback from the semi-structured interviews conducted. The interview results revealed divergent views representing the varying roles of the stakeholders in the education industry. Five categories of definitions were identified from the study. The first definition expressed by the majority of the respondents was fulfilling satisfaction and meeting stakeholders expectations whilst quality of graduates as well as teaching and learning were ranked second and third, illustrating moderate agreement from the respondents. The definitions accreditation and quality of lecturers were ranked fourth and fifth respectively, as the ones least agreed upon by the respondents of the present study.